Relationship between parameters of subclinical atherosclerosis and osteoporosis and their prognostic significance: data from the prospective studies - I. A. Skripnikova; M. A. Kolchina; O. V. Kosmatova; T. T. Tsoriev; O. Yu. Isaykina; O. M. Drapkina (Столичная издательская компания, 2023)
We analyzed modern publications on the relationship between cardiovascular diseases (CVDs) and osteoporosis and, in particular, their preclinical manifestations. Most of the papers on this issue are observational, cross-sectional, or study associations of preclinical markers with disease risk or outcomes. However, the results of these studies do not always coincide and are contradictory. Therefore, it is not possible to define cause-effect relationship between vascular changes and decreased bone mass, as well as persistence of its relationship. Due to the difficulties in management of prospective studies, in the last decade only a few studies have appeared with long-term follow-up of patients without symptoms with subsequent assessment of preclinical manifestations. A strong relationship has been demonstrated between intima-media thickness, plaque presence, coronary artery calcification and low bone density of the spine and proximal femur, as well as between vascular stiffness (pulse wave velocity) and proximal femur bone density. The data obtained indicate combined disorders of vascular wall morphology and bone tissue, not only in postmenopausal women, but also in elderly men, and can be used to justify indications for screening for decreased bone density in patients with CVD. At the same time, larger-scale prospective studies to explore associations between markers of preclinical manifestations of CVD and decreased bone mass, including in the Russian population, are required.